الرقمنة في قطاع التربية والتعليم في الجزائر -دراست حالة مديرية التربية ببرج بوعريريج - بلخيري سمير - بوهالي ام الخير (جامعة المسيلة, 2024)
Our study aimed to highlight the role of digitalization in improving and developing the education sector, especially in light of the significant transformations in information and communication technology and its substantial impact on individuals’ daily lives. Digitalization is considered a fundamental pillar for achieving a qualitative leap in the field of education, as it contributes to enhancing the quality of the educational process and facilitating access to information. The study addressed the concept and importance of digitalization, as well as its characteristics and objectives. It also reviewed the requirements and steps for implementing digitalization. Furthermore, the study focused on the applications of digitalization in the education sector, analyzing the current state of digitalization, its objectives, advantages, and challenges in this vital sector. We adopted the descriptive-analytical method in the theoretical part of our study, while a case study approach was used in the practical part to examine the Directorate of Education in the Wilaya of Bordj Bou Arreridj. The study included the ممخز الجراسة ~ 63 ~ organizational history of the directorate, its organizational structure, and the tasks and objectives it aims to achieve. The study reached several conclusions, including: - The importance of digitalization in improving the quality of education and facilitating the educational process. - The positive impact of digitalization on the management of educational institutions. - The challenges facing digitalization in the education sector and possible solutions to address them. Keywords: Digitalization, Education, Directorate of Education, Information Technology, Educational Development.